THE EFFECT OF COOPERATIVE SCRIPT METHOD ON THE SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 1 PEKANBARU - Eri Vianti; Eliwarti '; Afrianto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This pre-experimental study is aimed at finding out if there is a significant effect of Cooperative Script method on the speaking ability of the second year students of SMAN 1 Pekanbaru. The design of the study is one group pre-test-treatment-posttest design. 37 students of class XI MIA 1 in the second semester of academic year 2016/2017 were chosen as the sample by using Cluster random sampling. The instrument of the test was in the form of monologue and the treatment was conducted in six times. The students’ scores were graded by the three raters using Brown’s scale and analyzed using t-test formula.The results of the data analysis showed that the mean score of pre-test is 51.56 and the mean score of post-test is 67.44. The result showed that the value of t-test was higher than t-table (11,975>2,028) at the significance level 5% and at the significance level 2% (11,975>0,3810). Therefore, alternative hyphotesis (H1) is accepted and null hyphotesis (Ho) is rejected. It can be concluded that there is a significant effect of Cooperative Script method on the improvement of speaking ability of the second year students of SMAN 1 PekanbaruKeywords: Effect, Cooperative Script Method, Speaking Ability